Undescended testis. - Rafael Trinchet Soler; Manuel García Artiles; Ivonne López Masó; Leticia B. Montero Roca (Medisur)
Undescended testis constitute one of the most common congenital anomalies in newborn; it affects more than 3% of the children were born at the end of the gestation, and until 33% of premature infants. Surgical treatment reduces the risk of torsion, facilitates the exploration of the testicle, improves the endocrine function of the same one, make a scrotum with normal appearance and it is based on the theory that the early intervention prevents the secondary degeneration of the testicles caused by the high temperatures to those that it is subjected outside of the bag escrotal. We presented the Good Clinical Practices Guideline for Undescended testis, approved by consensus in the 4th National Good Clinical Practices Workshop in Pediatric Surgery (Las Tunas, Cuba; March 2005).